Central nervous system involvement and thrombocytopenia as predictors of mortality in children with hemophagocytic lymphohistiocytosis - Harnchoowong, Saralee; Soponkanaporn, Sirisucha; Vilaiyuk, Soamarat; Lerkvaleekul, Butsabong; Pakakasama, Samart (Frontiers in Pediatrics, 2022)
Introduction: Hemophagocytic lymphohistiocytosis (HLH) is a potentially life-threatening condition. This study aimed to evaluate treatment outcomes and identify prognostic-related factors in Thai children with HLH. Materials and methods: We retrospectively reviewed the medical records of 76 pediatric patients with HLH who were treated at Ramathibodi Hospital between January 2004 and December 2019. Treatment outcomes were defined as early mortality (death within 30 days after diagnosis) and early treatment response (resolution of all clinical features and normalization of at least one HLH-related laboratory parameter within 4 weeks). Results: The overall mortality rate was 38% (29/76), with an early mortality rate of 45% (13/29). Malignancy-associated HLH had the highest mortality rate (88%), followed by primary HLH (56%). The predictors of early mortality were central nervous system (CNS) involvement (OR 13 [95%CI 2–83], p=0.007) and platelet counts less than 44×106/mm3 (OR 8 [95%CI 1.3–49], p=0.024). The predictors of early treatment response were no CNS involvement (OR 6.6 [95%CI 1.5–28.8], p=0.011), platelet counts more than 44×106/mm3 (OR 8 [95%CI 2.1–30.9], p=0.003), and total bilirubin levels less than 1.8 mg/dL (OR 4 [95%CI 1.1–14.8], p=0.036). In the mixed-model analysis, platelet counts in non-survivors increased significantly less than those in survivors, with a mean difference in platelet changes between the two groups of 94.6×106/mm3 (p=0.003). Conclusion: The independent predictors of early mortality in children with HLH were CNS involvement and low baseline platelet counts. A slow rate of platelet increases during the first week after diagnosis was also associated with mortality.